Venoarterial Extracorporeal Membrane Oxygenation in Massive Pulmonary Embolism-Related Cardiac Arrest: A Systematic Review*. Issue 5 (May 2021) - Scott, John Harwood; Gordon, Matthew; Vender, Robert; Pettigrew, Samantha; Desai, Parag; Marchetti, Nathaniel; Mamary, Albert James; Panaro, Joseph; Cohen, Gary; Bashir, Riyaz; Lakhter, Vladimir; Roth, Stephanie; et al.
Abstract : OBJECTIVE: Management of patients experiencing massive pulmonary embolism-related cardiac arrest is controversial. Venoarterial extracorporeal membranous oxygenation has emerged as a potential therapeutic option for these patients. We performed a systematic review assessing survival and predictors of mortality in patients with massive PE-related cardiac arrest with venoarterial extracorporeal membranous oxygenation use. DATA SOURCES: A literature search was started on February 16, 2020, and completed on March 16, 2020, using PubMed, Embase, Cochrane Central, Cinahl, and Web of Science. STUDY SELECTION: We included all available literature that reported survival to discharge in patients managed with venoarterial extracorporeal membranous oxygenation for massive PE-related cardiac arrest. DATA EXTRACTION: We extracted patient characteristics, treatment details, and outcomes. DATA SYNTHESIS: About 301 patients were included in our systemic review from 77 selected articles (total screened, n = 1, 115). About 183 out of 301 patients (61%) survived to discharge. Patients ( n = 51) who received systemic thrombolysis prior to cannulation had similar survival compared with patients who did not (67% vs 61%, respectively; p = 0.48). There was no significant difference in risk of death if PE was the primary reason for admission or not (odds ratio, 1.62; p = 0.35) and if extracorporeal membranous oxygenation cannulation occurred in the emergency department versus other hospital locations (odds ratio, 2.52; p = 0.16). About 53 of 60 patients (88%) were neurologically intact at discharge or follow-up. Multivariate analysis demonstrated three-fold increase in the risk of death for patients greater than 65 years old (adjusted odds ratio, 3.08; p = 0.03) and six-fold increase if cannulation occurred during cardiopulmonary resuscitation (adjusted odds ratio, 5.67; p = 0.03). CONCLUSIONS: Venoarterial extracorporeal membranous oxygenation has an emerging role in the management of massive PE-related cardiac arrest with 61% survival. Systemic thrombolysis preceding venoarterial extracorporeal membranous oxygenation did not confer a statistically significant increase in risk of death, yet age greater than 65 and cannulation during cardiopulmonary resuscitation were associated with a three- and six-fold risks of death, respectively. Abstract : Supplemental Digital Content is available in the text.